Systematic identification of TPS genes in Gossypium and their characteristics in response to flooding stress - Cui, Aihua; Jin, Yunqian; Li, Yongqi; Nie, Taili; Sun, Liangqing (Frontiers in Plant Science, 2023)
Terpene synthases (TPS) is a key enzyme in the synthesis of plant terpenoids. Studies on TPSs have not been reported in Gossypium barbadense and Gossypium arboreum. 260 TPSs were identified in Gossypium, including 71 in Gossypium hirsutum, 75 in Gossypium barbadense, 60 in Gossypium arboreum, and 54 in Gossypium raimondii. We systematically analyzed the TPS gene family of Gossypium from three aspects: gene structure, evolutionary process and gene function. (1) Gene structure: Based on the protein structure of two conserved domains (PF01397 and PF03936), the TPS gene family is divided into five clades: TPS -a, -b, -c, -e / f and -g. (2) Evolution: Whole genome duplication and segmental duplication are the main modes of TPS gene amplification. (3) Function: The abundance of cis-acting elements may reveal the functional diversity of TPSs in cotton. TPS gene has tissue specific expression in cotton. The hypomethylation of the exon of TPSs may help to enhance the adaptability of cotton to flooding stress. In conclusion, this study can broaden the understanding of structure-evolution-function of the TPS gene family, and provide reference for the mining and verification of new genes.